Eccentric and Isometric Exercises in Achilles Tendinopathy Evaluated by the VISA-A Score and Shear Wave Elastography. (July 2020) - Gatz, Matthias; Betsch, Marcel; Dirrichs, Timm; Schrading, Simone; Tingart, Markus; Michalik, Roman; Quack, Valentin
Background: Apart from eccentric exercises (EE), isometric exercises (ISO) might be a treatment option for Achilles tendinopathy. Shear wave elastography (SWE) provides information for diagnosis and for monitoring tissue elasticity, which is altered in symptomatic tendons. Hypothesis: Isometric exercises will have a beneficial effect on patients' outcome scores. Based on SWE, insertional and midportion tendon parts will differ in their elastic properties according to current symptoms. Study Design: Randomized clinical trial. Level of Evidence: Level 2. Methods: Group 1 (EE; n = 20; 12 males, 8 females; mean age, 52 ± 8.98 years) and group 2 (EE + ISO; n = 22; 15 males, 7 females; mean age, 47 ± 15.11 years) performed exercises for 3 months. Measurement points were before exercises were initiated as well as after 1 and 3 months using the Victorian Institute of Sports Assessment–Achilles (VISA-A) score, American Orthopaedic Foot & Ankle Society score, and SWE (insertion and midportion). Results: Both groups improved significantly, but there were no significant interindividual differences (VISA-A; P = 0.362) between group 1 (n = 15; +15 VISA-A) and group 2 (n = 15; +15 VISA-A). The symptomatic insertion (symptomatic, 136.89 kPa; asymptomatic, 174.68 kPa; P = 0.045) and the symptomatic midportion of the Achilles tendon (symptomatic, 184.40 kPa; asymptomatic, 215.41 kPa; P = 0.039) had significantly lower Young modulus compared with the asymptomatic tendons. The midportion location had significantly higher Young modulus than the insertional part of the tendon ( P = 0.005). Conclusion: Isometric exercises do not have additional benefit when combined with eccentric exercises, as assessed over a 3-month intervention period. SWE is able to distinguish between insertional and midportion tendon parts in a symptomatic and asymptomatic state. Clinical Relevance: The present study shows no additional effect of ISO when added to baseline EE in treating Achilles tendinopathy. Different elastic properties of the insertional and midportion tendon have to be taken into consideration when rating a tendon as pathologic.